Transcript and metabolic adjustments triggered by drought in Ilex paraguariensis leaves - Acevedo, Raúl Maximiliano (2019)
Ilex paraguariensis (yerba mate) is cultivated in the subtropical region of South America, where the occurrence of drought episodes limit yield. To explore the mechanisms that allow I. paraguariensis to overcome dehydration, we investigated (1) how gene expression varied between water-stressed and non-stressed plants and (2) in what way the modulation of gene expression was linked to physiological status and metabolite composition. A total of 4920 differentially expressed transcripts were obtained through RNA-Seq after water deprivation. Drought induced the expression of several transcripts involved in the ABA-signalling pathway. Stomatal closure and leaf osmotic adjustments were promoted to minimize water loss, and these responses were accompanied by a high transcriptional remodeling of stress perception, signalling and transcriptional regulation, the photoprotective and antioxidant systems, and other stress-responsive genes. Simultaneously, significant changes in metabolite contents were detected. Glutamine, phenylalanine, isomaltose, fucose, and malate levels were shown to be positively correlated with dehydration. Principal component analysis showed differences in the metabolic profiles of control and stressed leaves. These results provide a comprehensive overview of how I. paraguariensis responds to dehydration at transcriptional and metabolomic levels and provide further characterization of the molecular mechanisms associated with drought response in perennial subtropical species.